Pelatihan Penggunaan Aplikasi Mobile Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah di Galleries Abata - Dita Nurmadewi; Jurica Lucyanda; Anastasya Andriarti; Haris Rafi; Ni Kadek Srimanik; Komang Ayu Sumariasih (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting the national economy, yet they still face challenges, particularly in maintaining financial records and reporting in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM). Abata Galleries MSME, as the partner in this activity, previously did not have a structured financial recording system, thus requiring technology-based assistance. This training activity aims to strengthen financial literacy and bookkeeping skills through the use of the KASIU mobile application based on SAK EMKM. The methods applied included a pre-test, material presentation, hands-on practice with the application, a post-test, and an evaluative discussion. The results of the activity indicate a significant improvement in participants’ understanding of SAK EMKM as well as their skills in preparing financial reports in accordance with the standards using the KASIU application. Participants who previously had no knowledge of SAK EMKM are now able to comprehend and implement standardized financial recording. This activity also fostered behavioral changes, particularly the awareness of the importance of maintaining structured daily records, thereby supporting transparency, accountability, and business sustainability.